INSTITUTIONAL CHANGES IN THE SOCIO-ECONOMIC LIFE OF SOCIETY ON THE BASIS OF DIGITAL INCLUSION AND SECURITY - K.M. Kraus (Aktualʹnì Problemi Rozvitku Ekonomìki Regìonu, 2025)
The article is devoted to the issue of digital transformation of the economy, which affects the digital quality of life of the countryʼs citizens and their well-being. The purpose of the study is to review the dynamics, causes and consequences of changes in the rating of Ukraine according to the Digital Quality of Life index in 2021–2023, as well as the development of proposals to increase the return and socio-economic effects of the implementation of digital technologies and solutions to ensure the growth of the digital quality of life in the countryʼs society. In order to achieve the goal, analysis and synthesis, generalization and comparison, graphic and statistical methods were used, which in the complex made it possible to present scientific developments in an argumentative manner, which will be useful for both theoreticians and practitioners. The article carried out a deep and comprehensive analysis of the rating of Ukraine according to the Digital Quality of Life index in general and by categories (Internet availability, Internet quality, electronic infrastructure, electronic security and electronic government) in 2021–2023, and made it possible to identify the current state of affairs with processes digitization of the economic and social life of society, as well as outline potential opportunities for economic growth. The scientific novelty of the research lies in the presented heat map of the rating of Ukraine according to the Digital Quality of Life index in 2021–2023, which not only visualizes the country’s position according to this index and in the cross-section of its elements on the world map, but also instantly demonstrates the strengths and weaknesses of digital transformations in the country. The practical significance of the article is outlined by the provided practical recommendations on strengthening the security, accessibility and inclusiveness of digital solutions and transformations in the country in order to increase the level of the digital quality of life of Ukrainian society, as well as creating a reliable basis for the future economic recovery of Ukraine and its prosperity.